Influence of seamless nursing model of humanistic care on nursing quality and blood infection risk of neurosurgical ICU patients and its correlation with APACHE II score - Liu, Fuhua; Wang, Xiaoting (Frontiers in Public Health, 2022)
Objective:To explore the impact of seamless nursing mode based on humanistic care on nursing quality and blood infection risk of ICU patients in neurosurgery and its correlation with APACHEⅱscore.Methods:A total of 110 ICU patients admitted to our hospital from September 2020 to January 2021 were selected for this study.They were divided into control set and study set according to the order of admission,with 55 patients in each set.The control set was given the previous routine nursing mode,and the study set was given the seamless management under humanistic care.The nursing quality of the two sets was contrast.Blood infection rate was contrast between the two sets.The anxiety and depression before and after nursing were contrast between the two sets.The nursing satisfaction of the two sets was contrast.APACHEⅱscore was contrast between the two sets.The correlation between patient nursing quality score,blood infection and APACHEⅱscore was contrast.Results:The scores of nursing quality in the study set were notoriously higher than those in the control set(all P<0.05).The risk rate of blood infection in the study set was 5.45%,which was notoriously lower than that in the control set(25.45%)(P<0.05).Before nursing,there were no large differences in SAS and SDS scores between 2 sets(P>0.05);After nursing,SAS and SDS scores of 2 sets were decreased,and the study set was lower than the control set(P<0.05);The overall satisfaction of nursing in the study set was 89.09%,notoriously higher than that in the control set(63.64%)(P<0.05).Before nursing,APACHEⅱscore was higher in both sets,and the difference was not statistically large(P>0.05).After nursing,APACHEⅱscore was improved in both sets,and the improvement effect in the study set was notoriously better than that in the control set(P<0.05).There was large negative correlation between nursing quality scores and APACHEⅱscores(P<0.05).There was a large negative correlation between the risk of blood infection and APACHEⅱscore(P<0.05).Conclusion:For ICU patients in neurology department,the application of seamless nursing mode based on humanistic care can improve the quality of care,reduce the risk of blood infection and APACHEⅱscore,promote the recovery of patients,improve the prognosis of patients,and is worthy of clinical application.